A perspective on the rise and fall of the energy regulator in Britain. (April 2016) - Thomas, Steve
Abstract: The process of Electricity Market Reform instigated in 2010 is leading to fundamental reforms to the UK electricity market. Despite its previous strong presence in the policy process, the British energy market regulator, OFGEM, appears to have only a minimal role in the implementation of these reforms. This article reviews the history of OFGEM, including expectations for the agency when it was established and how it evolved over time. From this perspective, several factors that might have contributed to OFGEM's apparent marginalisation are identified. These include perceptions of a poor track record, a tendency of governments to bypass the regulator for decisions deemed important, and the subordination of economic issues to climate-change priorities. Highlights: Expectations that energy regulation could be 'light-handed' have proved unrealistic. Attempts to make electricity markets competitive have had limited success. While energy market prices were low, government left decisions to the regulator.